L’effet structurant du contrôle social - Cusson, Maurice (Criminologie, 1993)
The paper deals with the following question. To what extent do the human efforts at controlling crime succeed ? It starts by proposing an enlarged concept of social control. In the second part, a theory of choices made by offenders under the constraint of social control is put forward. In the last part, it is argued that social control can have four types of impacts :I — reducing the frequency of crime; 2 — reducing its severity; 3 — rendering obsolete some criminal tactics and stimulating the development of new ones; and, 4 — channeling offenders toward vulnerable targets. It is concluded that crime is shaped by the means used to control it, meaning that a given state of crime rates should be seen as the result of what people decide to do and not to do about crime.